Inter-firm network strategies of Korean firms in Malaysia - Kim, Won Ik (2020)
Over the past few decades, outward investment has been brisk, with the aim of relocating production facilities to areas where the production costs are low or the sales market are expanding. With globalisation as the driving force of development, inter-firm network has become an important factor to continue business activities with relatively better competitiveness. Inter-firm networks are essential to procure necessary resources locally or from overseas and maximise profits for firms investing in developing countries. This research, which focuses on Korean firms, aims to explore the intricacies of the network relationships between buyers and suppliers. Since the influence and strategies of the inter-firm network of overseas Korean firms have not been satisfactorily explored yet, this study attempts to fill the gap by exploring the motives and selection criteria, as well as the benefits and challenges of Korean inter-firm networks in Malaysia. In addition, the study also explores the influence of the inter-firm network towards organizational performance, role of parent company and sourcing strategies of Korean firms in the Malaysian electronics and steel manufacturing industry. This study used the qualitative case study method to answer the research questions. Firms were chosen from the Klang Valley area in Malaysia with a major concentration of Korean companies. Data were collected from in-depth interviews with key decision-makers at six electronics and steel Korean companies in Malaysia. This study investigated the nature of Korean inter-firm network by analysing the business activities of two types of Korean companies, namely Korean subsidiaries (with the headquarters in South Korea) and Korean companies founded in Malaysia. The results of this study have shown that linkages with external entities are very important for the success of inter-firm network. The findings revealed that trust, capacity, reputation, and nationality were important factors among the Korean firms and these factors played an important role in strengthening the business network among Korean firms in Malaysia. Besides, there were three main motives for Korean firms to establish inter-firm networks with suppliers in Malaysia. The firms emphasised on locational decisions, low-cost sourcing, and easiness for procurement. In addition, long-term relationships would be helpful to strengthen and stabilise the network among the parties. Furthermore, the benefits of Korean firms having inter-firm network can be summarised into seven points: improved lead time and availability, ease of communication, long-term relationship, lower stock holdings at Korean multinational corporations or other MNCs (end-user), routine material information, trust relationship, and information sharing. In contrast, Korean firms took a passive attitude towards local suppliers due to the concern of leakage of confidential information, leak of communication, and maladaptation of the typical Korean business style. Theoretically, the study has applied the Industrial Network and Social Capital theories in explaining the various attitude and behaviour of Korean firms in networking with their suppliers. The study contributes also the the in-depth knowledge of the intricacies of overseas Korean inter-firm strategic behaviour. Practically, the study highlighted the favourable inclination of Korean firms to other Korean-owned firms as their suppliers. However, non-Korean companies are suggested to penetrate the networks of Korean firms by initiating informal relationships, building trust and focusing on long-term relationships.